PENGARUH KUALITAS PRODUK DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN - Alwan Hendri; Widi Dewi Ruspitasari; Mohammad Bukhori (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
One of the typical foods of the Riau region is Ketan talam durian which was introduced by Rumah Kue Viera which is very delicious, its development is extraordinary.. The purpose of this research is to find out and analyze 1) the effect of product quality on Repurchase Decision 2) the effect of Brand Awereness on Repurchase Decision, 3) the effect of product quality on customer satisfaction, 4) the effect of Brand Awereness on customer satisfaction,5) the effect of customer satisfaction on Repurchase Decision, 6) the effect of product quality on Repurchase Decision through customer satisfaction, 7) the effect of Brand Awereness on Repurchase Decision through customer satisfaction. This study uses a quantitative descriptive approach to Viera Cake House customers. The research population is Viera Cake House customers who have shopped more than once in Mey 2023 with a research sample of 100 respondents using an accidental sampling technique. The inferential statistical analysis technique uses the Partial Least Square (PLS) technique with the SmartPLS 4.0 tool. The test instruments used are validity and reliability tests, outer model construction tests, discriminant validity tests with the Fornell-Larckel Criterion and the AVE method, Inner Model R-Square, Q-Square and GoF tests, Bootstrapping hypothesis testing,, the results show 1) product quality affects customer satisfaction 2) Brand Awareness affects customer satisfaction 3) product quality affects repurchase decisions, 4) Brand Awareness affects repeat purchase decisions, 5) customer satisfaction does not have a significant effect on repurchase decisions 6) product quality does not affect repurchase decisions through customer satisfaction 7) Brand Awareness does not affect repurchase decisions through customer satisfaction.